2020
DOI: 10.20452/pamw.15316
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cytogenetic evolution and acquisition of del(17p) on the prognosis of multiple myeloma patients

Abstract: Prognostic impact of cytogenetic evolution in multiple myeloma 483 transplant (auto -HSCT) 11 have significantly improved the prognosis of patients with MM. However, most cases of MM are still incurable.Recent studies using next -generation sequencing (NGS) approaches have provided evidence that MM is characterized by spatial and temporal genetic heterogeneity and is composed of multiple populations of genetically distinct subclones, which evolve over time following a pattern INTRODUCTION Multiple myeloma (MM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…To further explore the added predictive value of cytogenetic variables, subsets with FISH-defined chromosome abnormalities and GEP were extracted. We conducted an assessment of the prognostic significance of various chromosomal aberrations, including deletion (17p del) [ 30 ], gain (1q gain) [ 31 ], and translocation (4;14, 14;16) [ 32 ], as well as gene expression profile (GEP) scores within specific cytogenetic subsets ( Supplemental Tables S8–S11 ). The incorporation of these genetic signatures demonstrated an enhancement in the c-index, indicating improved prognostic accuracy.…”
Section: Resultsmentioning
confidence: 99%
“…To further explore the added predictive value of cytogenetic variables, subsets with FISH-defined chromosome abnormalities and GEP were extracted. We conducted an assessment of the prognostic significance of various chromosomal aberrations, including deletion (17p del) [ 30 ], gain (1q gain) [ 31 ], and translocation (4;14, 14;16) [ 32 ], as well as gene expression profile (GEP) scores within specific cytogenetic subsets ( Supplemental Tables S8–S11 ). The incorporation of these genetic signatures demonstrated an enhancement in the c-index, indicating improved prognostic accuracy.…”
Section: Resultsmentioning
confidence: 99%
“…However, in this study, there was no difference in IgH rearrangement between the RI and no-RI groups. The incidence of RI with positive chromosome 17 deletion detected during MM treatment has been reported to be higher in the RI group compared to the no-RI group, which were 12.5% and 6.9,% respectively ( 18 ). However, in this study, there was no difference between the RI and no-RI groups.…”
Section: Discussionmentioning
confidence: 98%
“…We and others have previously shown that the evolution of cytogenetic aberrations over time has prognostic significance in MM [ 51 , 52 , 53 ]. Recently, Yan et al performed a single-cell analysis using quantitative multi-gene FISH on 129 longitudinally sampled specimens from 57 MM patients confirming that patients with stable cytogenetic structure achieve significantly longer survival than patients with evolutionary dynamics [ 54 ].…”
Section: Discussionmentioning
confidence: 99%